A study of Acrylonitrile butadiene styrene properties for immobilization device in neonate chest radiography - Insawang, Pimpravee; Watcharasiranon, Pakwipa; Cheewakul, Jongwat; Ina, Natee; Chairerk, Patcharee (The Thai Journal of Radiological Technology, 2019)
Introduction: The neonatal chest radiography was difficult and took for a long time because the infants used to cry and move during X-ray. It causes the radiography has poor quality and need to retake the X-ray that increase unnecessary radiation dose to infants. We realize to the complicated of infants positioning. Then, we created an immobilization device for neonates in chest radiography to keep infants are not to move while doing the X-ray radiography. Objective: The purpose of this project is to test the properties of the infant’s immobilization device was made from Acrylonitrile butadiene styrene materials in the chest radiography and to answer the questionnaire of personnel on the infant’s immobilization device in X-ray room no.3, Department of Radiology and Neonatal Moderate Intensive Care Units (NMCU) and Nursery ward at Songklanakarind Hospital. Materials and methods: The infant’s immobilization device was made from Acrylonitrile butadiene styrene which has been molded to look like a block of baby. We used velcro tape to immobilize infants. Then, we took the device to measure the radiation dose from RaySafe X2 dosimeter, and to test the strength by Finite Element Method. In addition, the personnel are including the nurses for NMCU and radiologic technologists answered the questionnaire to the immobilization device. Results: From the comparison between the X-ray quantity through the air and Acrylonitrile butadiene styrene (ABS) are different by 5.48%. From the strength test of the immobilization device that use the Finite element analysis, it was found that the highest force of the device received in each case which legs lift, legs lift and both arms lift, legs lift and left arm lift, both arms lift, left arm lift and no lift was 2.149, 6.794, 6.374, 6.754, 6.268 and 2.655 MPa, respectively. The results of questionnaire from the personnel for the neonate immobilization are revealed that the strongly agree is about a strong structure which can support the infants. And there are 63.64% with the properly size, and weight. The second is they are easy to use, fast and convenient. Moreover, they can be used in the future by 54.55% and suitable to the infant’s movement that limit by 36.36%. Conclusions: The infant immobilization device can be used without increasing exposure parameters (kVp and mAs). Moreover, it was strong and durable to the muscle strength of infants. And received the strongly agree as for the strong structure which can support the weight of the infants and the device which has the appropriate size and weight.